Morocco : 2021 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
Thanks to a successful vaccination campaign, COVID19 cases have declined sharply in 2021, and the Moroccan economy is rebounding. Economic activity has recovered most of the ground lost with the severe recession of 2020 and is expected to grow at 6.3 percent in 2021. Among the factors propelling the rebound are the exceptional harvest after two years of drought, continued fiscal and monetary stimulus, and the persistent buoyancy of remittances. Going forward, Morocco's growth is expected to remain at about 3 percent, assuming the acceleration of new cases in early 2022 proves transitory and the effects of the pandemic on activity gradually fade. Recent inflationary pressures remained manageable and are expected to wane in 2022, as cost pressures from global and domestic supply disruptions are reabsorbed. After its sharp contraction in 2020, the current account deficit is projected to widen in 2021 and over the medium term, but Morocco emerges from the pandemic with a much stronger international reserve position.